2004
DOI: 10.1088/1126-6708/2004/07/030
|View full text |Cite
|
Sign up to set email alerts
|

Gauged Gravity via Spectral Asymptotics of non-Laplace type Operators

Abstract: We construct invariant differential operators acting on sections of vector bundles of densities over a smooth manifold without using a Riemannian metric. The spectral invariants of such operators are invariant under both the diffeomorphisms and the gauge transformations and can be used to induce a new theory of gravitation. It can be viewed as a matrix generalization of Einstein general relativity that reproduces the standard Einstein theory in the weak deformation limit. Relations with various mathematical co… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
73
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(75 citation statements)
references
References 27 publications
2
73
0
Order By: Relevance
“…However, in [7] all gravitons have unbroken U(N) symmetry and are all massless which is non-physical. More recently he obtained a unique gravity action based on the spectral expansion of non-Laplace type operator [8]. That formulation differs from the approach considered here as we take the mixing between the SL(2, C) space-time symmetry and the U(N) internal symmetry to be non-trivial, and where after symmetry breaking, all gravitons except one become massive.…”
Section: Introductionmentioning
confidence: 97%
“…However, in [7] all gravitons have unbroken U(N) symmetry and are all massless which is non-physical. More recently he obtained a unique gravity action based on the spectral expansion of non-Laplace type operator [8]. That formulation differs from the approach considered here as we take the mixing between the SL(2, C) space-time symmetry and the U(N) internal symmetry to be non-trivial, and where after symmetry breaking, all gravitons except one become massive.…”
Section: Introductionmentioning
confidence: 97%
“…For non-Laplace operators on manifolds without boundary even the invariant A 4 is not known, in general (for some partial results see [13,10,12] and the review [14]). For natural non-Laplace type differential operators on manifolds without boundary the coefficients A 0 and A 2 were computed in [13].…”
Section: Thus the Geometric Aspect Of The Spectral Asymptotics Of mentioning
confidence: 99%
“…Seeley [42] showed that there are no logarithmic terms in the asymptotic expansion of the trace of the heat kernel, which are possible on general grounds, and that the heat invariants do depend on the boundary condition at the singular set; the neglect of that simple fact lead to some controversy on the coefficient A 2 in the past until this question was finally settled in [42,11]. [8,9,10,12], when instead of a single Riemannian metric there is a matrixvalued symmetric 2-tensor, which we call a "non-commutative metric". Matrix geometry is motivated by the relativistic interpretation of gauge theories and is intimately related to Finsler geometry (rather a collection of Finsler geometries) (see [8,9,10]).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Only the total mass of a gravitating particle is observed. For more details and discussions see [2,3].…”
Section: Introductionmentioning
confidence: 99%